Endophthalmitis after dropless (Tri-Moxi injection) cataract surgery. Issue 5 (September 2020) - Ng, Caleb; Chalam, Kakarla V
Introduction: A case of endophthalmitis after dropless cataract surgery with intravitreal Tri-Moxi associated with severe vision loss. Case summary: An 82-year-old male developed severe vision loss in the left eye 24 days after dropless cataract surgery with intravitreal Tri-Moxi injection. Best corrected visual acuity was hand motion in the left eye. Intraocular pressure was 13, with inferior keratic precipitates, 4 + cell with 1 mm layered hypopyon, and a plaque on the posterior capsule that blocked direct exam of the posterior segment. Ultrasonography revealed extensive vitritis without retinal or choroidal detachments. Conclusion: Endophthalmitis resolved and vision improved after management with vitreous tap, intravitreal and fortified topical antibiotics, and subsequent prompt pars plana vitrectomy. Vitreous sample grew fluoroquinolone-resistant staphylococcus epidermidis.